2014
DOI: 10.2320/matertrans.m2014159
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Tool Life of Friction-Stir-Welded DP590 Using the Si<sub>3</sub>N<sub>4</sub> Tool

Abstract: Early studies have been conducted on the friction stir welding of steel, tungsten (W), molybdenum (Mo), tungsten carbide, and the like for the production of tools, but the tool materials were significantly worn out and deformed while they were being joined. So far, the polycrystalline cubic boron nitride (PCBN) tool, which is very strong at high temperatures and is wear-resistant, has performed relatively well, but the improvement of its productivity is limited by its high manufacturing cost. In this study, 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The adoption of FSW for steels has quite lagged behind Al alloys since the first-generation tools were insufficient regarding their high-temperature strength, wear resistance and fracture toughness, although some initial feasibility studies on the FSW of steels were conducted by Thomas in 1999 [37]. It was then possible to weld 12 mm thick steel at a rate over 1 m min −1 by FSW [27] due to the rapid advance in tools such as WC-based-alloy tools [38][39][40][41], Si 3 N 4 tools [42][43][44], iridium-alloy tools [45] and polycrystalline cubic boron nitride (PCBN) tools [46][47][48], which suggested that the FSW technique started to become realistic to be used for steels.…”
Section: Steelsmentioning
confidence: 99%
“…The adoption of FSW for steels has quite lagged behind Al alloys since the first-generation tools were insufficient regarding their high-temperature strength, wear resistance and fracture toughness, although some initial feasibility studies on the FSW of steels were conducted by Thomas in 1999 [37]. It was then possible to weld 12 mm thick steel at a rate over 1 m min −1 by FSW [27] due to the rapid advance in tools such as WC-based-alloy tools [38][39][40][41], Si 3 N 4 tools [42][43][44], iridium-alloy tools [45] and polycrystalline cubic boron nitride (PCBN) tools [46][47][48], which suggested that the FSW technique started to become realistic to be used for steels.…”
Section: Steelsmentioning
confidence: 99%
“…Though much research works are available on friction stir welding variants [14][15][16][17][18] of AHSS, they are limited to microstructural characteristics and basic mechanical properties in basic lap configuration. However, to gain more understanding and confirm the feasibility of using AHSS for energy absorbing and other structural applications, a study on friction stir welding on lap configuration, i.e., friction stir lap welding (FSLW) and friction stir spot lap welding (FSSLW), must be studied in detail.…”
Section: Introductionmentioning
confidence: 99%